2022
DOI: 10.3390/s22207930
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Load Balancing Scheme for Satellite IoT Networks Based on Spatial–Temporal Distribution of Users and Advanced Genetic Algorithms

Abstract: Satellite IoT networks (S-IoT-N), which have been a hot issue regarding the next generation of communication, are quite important for the coming era of digital twins and the metaverse because of their performance in sensing and monitoring anywhere, anytime, and anyway, in more dimensions. However, this will cause communication links to face greater traffic loads. Satellite internet networks (SIN) are considered the most possible evolution road, possessing characteristics of many satellites, such as low earth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, the authors concluded that trajectory-based policies can duplicate the amount of served IoT nodes. Departing from LoRa-based networks, a resource allocation scheme based on genetic algorithms for load balancing was provided in [23]. Therein, problems such as low efficiency in extremely non-uniform user distribution conditions and density variations were detected.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the authors concluded that trajectory-based policies can duplicate the amount of served IoT nodes. Departing from LoRa-based networks, a resource allocation scheme based on genetic algorithms for load balancing was provided in [23]. Therein, problems such as low efficiency in extremely non-uniform user distribution conditions and density variations were detected.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, unlike the policies proposed in [16], our method generates a collision-free channel access strategy that can be implemented with low computational complexity, so it can even be run on-board the satellite if necessary. Finally, concerning [23], [24], our proposed approach is tailored for LoRa-based DtS-IoT networks, with low computational complexity and high effectiveness despite the dynamics of these scenarios.…”
Section: Related Workmentioning
confidence: 99%